The level of HIV/AIDS knowledge amongst female young adults and factors that inhibit hem from negotiating condom usage - Mnqayi, Carol Velile (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.